Nurt instytucjonalny we współczesnej myśli ekonomicznej - Ratajczak, Marek (Wydział Prawa i Administracji UAM, 1994)
The paper deals with a description of institutionalism and focuses on its contemporary form - the so-called neo-institutionalism. The main three parts relate to: (1) characteristics and criticism of neo-institutionalism; (2) the relationship between neo-institutionalism and the mainstream economics; (3) the relationship between neo-institutionalism and the new institutional economics. In the authors opinion neither neo-institutionalism nor the new institutional economics should be seen as alternatives to the mainstream economics. Instead, an attempt should be made to combine their strengths and achievements in order to provide a better explantation of the market economy mechanisms In conclusion, attention is paid to the applicability of neo-institutionalism and of the new institutional economics to the analysis of transition from a centrally planned to a free market economy. Many of the related phenomena (inertia and slow evolution of institutions as obstacles to the economic transition) are best explicable on the level of institutional analysis. In this context neo-institutionalism seems more useful for macroeconomists, whereas the new institutional economics can be of help both to mezo- and microeconomists
The institutional trend in contemporary economic thought